Radiofrequency coil for routine ultra‐high‐field imaging with an unobstructed visual field. (10th December 2020) - Gilbert, Kyle M.; Klassen, L. Martyn; Mashkovtsev, Alexander; Zeman, Peter; Menon, Ravi S.; Gati, Joseph S.
Abstract : Many neuroscience applications have adopted functional MRI as a tool to investigate the healthy and diseased brain during the completion of a task. While ultra‐high‐field MRI has allowed for improved contrast and signal‐to‐noise ratios during functional MRI studies, it remains a challenge to create local radiofrequency coils that can accommodate an unobstructed visual field and be suitable for routine use, while at the same time not compromise performance. Performance (both during transmission and reception) can be improved by using close‐fitting coils; however, maintaining sensitivity over the whole brain often requires the introduction of coil elements proximal to the eyes, thereby partially occluding the subject's visual field. This study presents a 7 T head coil, with eight transmit dipoles and 32 receive loops, that is designed to remove visual obstructions from the subject's line of sight, allowing for an unencumbered view of visual stimuli, the reduction of anxiety induced from small enclosures, and the potential for eye‐tracking measurements. The coil provides a practical solution for routine imaging, including a split design (anterior and posterior halves) that facilitates subject positioning, including those with impaired mobility, and the placement of devices required for patient comfort and motion reduction. The transmit and receive coils displayed no degradation of performance due to adaptions to the design topology (both mechanical and electrical) required to create an unobstructed visual field. All computer‐aided design files, electromagnetic simulation models, transmit field maps and local specific absorption rate matrices are provided to promote reproduction. Abstract : A 7 T head coil is presented that is designed to remove obstructions from the subject's visual field, allowing for an unimpeded presentation of stimuli during functional imaging and reduced anxiety due to the confines of the MRI environment. The coil provides a practical solution for routine imaging, including a split‐housing design that accommodates the positioning of subjects. All computer‐aided design files, electromagnetic simulation models, local specific absorption rate matrices and transmit field maps are provided to promote reproduction.